2008
DOI: 10.1007/s00249-008-0376-y
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of the specific PapG–galabiose binding in E. coli P pili-mediated adhesion

Abstract: Detailed analyses of the mechanisms that mediate binding of the uropathogenic Escherichia coli to host cells are essential, as attachment is a prerequisite for the subsequent infection process. We explore, by means of force measuring optical tweezers, the interaction between the galabiose receptor and the adhesin PapG expressed by P pili on single bacterial cells. Two variants of dynamic force spectroscopy were applied based on constant and non-linear loading force. The specific PapG-galabiose binding showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 41 publications
4
27
0
Order By: Relevance
“…These observations underpin some flexibility of type 1 fimbriae structures, probably depending on their physiological state, in line with previous conclusions. 5,[16][17][18] Impact of pH and pulling rate on FimH-mannose interaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations underpin some flexibility of type 1 fimbriae structures, probably depending on their physiological state, in line with previous conclusions. 5,[16][17][18] Impact of pH and pulling rate on FimH-mannose interaction.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that both pili are highly flexible and they may be viewed as dynamic structures with spring-like properties. 5,[16][17][18] Indeed, when bacteria were subjected to hydrodynamic constrains, these structures maintain bacterial attachment to host cells or surfaces by reducing the impact of flushes and associated mechanical stress 5,19 following an unwinding of the pointed out that the length of P-pili and type 1 fimbriae could increase by a factor 5 following such unwinding process under high shear stress conditions. [20][21][22] The forced unraveling of type 1 fimbriae is reversible, with helical rewinding taking place for shear forces of magnitude ~ 60 pN.…”
Section: Introductionmentioning
confidence: 99%
“…The pilus was exposed to further discontinuities at forces outside the range of the plot, why the retraction curve appears shifted from the elongation curve. Dashed curves: fits of Equation (1) As was alluded to above, the persistence length of T4 pili was assessed to 2.1 AE1.7 nm, which is similar to the length of a RrgB subunit, but slightly shorter than those of P and type 1 pili previously found to be 3.3 AE 0.6 nm [21] and 3.3 AE 1.6 nm, [17] respectively. This suggests that T4 pili have a structure that is significantly more flexible than closed helix-like pili, and similar to, or slightly more flexible than, open helix-like pili, expressed by UPEC.…”
Section: Discussionmentioning
confidence: 99%
“…The adhesins do appear to be adapted to their particular environment; FimH has a 'catch bond' which allows the adhered bacteria to withstand the high pressure urine flows of the bladder, whereas the P pilus has a 'slip bond', suitable for the more regular flows of the kidneys, which allows for maximum dissemination of bacteria [63][64][65].…”
Section: Preventing Growth Of the Pilus With Pilicidesmentioning
confidence: 98%